Pengaruh Likuiditas,Kepemilikan Manajerial Dan Kepemilikan Institusional Terhadap Kebijakan Hutang (Studi Kasus pada Perusahaan Sektor Transportasi Pada tahun 2015-2019) - M. Farchan Fuadi; Ronny Malavia Mardani; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the effect of liquidity, managerial ownership and institutional ownership policies on the company (a case study on the transportation sector in 2015-2019). The variables used in this study are related variables are liabilities, while the independent variables are liquidity, managerial ownership, and institutional ownership. The results of this study partially show that liquidity has a negative and significant effect on debt. partially shows that managerial ownership has a positive and significant effect on debt policy. Based on the partial test results indicate that institutional ownership has a positive and significant effect on debt policy.Keywords: influence of liquidity, managerial ownership, institutional ownership, debt policy